2019
DOI: 10.5897/jpp2019.0543
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, acute toxicity and blood profile of albino rats treated with fruit extract of Solanum macrocarpon

Abstract: Phytochemical screening of the methanolic fruit extract of Solanum macrocarpon was performed using standard method. Eighteen male albino mice, assigned into six groups (n=3) were used to determine the acute toxicity (LD 50) of the extract. Haematological effect of the extract was determined using forty eight adult male rats assigned into four groups (A-D; n=12). The treatment groups received daily oral administration of the extract at doses of 400, 800 and 1600 mg/kg of body weight (bw) respectively for 21 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Significant (p˂0.05) changes occurred in red blood cells count, hemoglobin, lymphocytes and MID of rats treated with the extract compared to control. These results were not confirmed by those of Mbegbu et al [35] . Hemoglobin is important in the transfer of respiratory gases in the body and in maintaining the acid/base balance [36] .…”
Section: Effect Of Oral Administration Of S Aethiopicum Leaves Extract On Some Biochemical Parameterscontrasting
confidence: 78%
See 1 more Smart Citation
“…Significant (p˂0.05) changes occurred in red blood cells count, hemoglobin, lymphocytes and MID of rats treated with the extract compared to control. These results were not confirmed by those of Mbegbu et al [35] . Hemoglobin is important in the transfer of respiratory gases in the body and in maintaining the acid/base balance [36] .…”
Section: Effect Of Oral Administration Of S Aethiopicum Leaves Extract On Some Biochemical Parameterscontrasting
confidence: 78%
“…Our results showed a significant (p˂0.05) increase in lymphocytes of rats treated with the extract when compared to the controls. Mbegbu et al [35] showed that the administration of methanoic extracts from the fruits of S. macrocarpon to rats at doses of 400, 800 and 1600 mg/kg increased the number of white blood cells. An increased number of lymphocytes is observed in the activation of the defense system, inflammatory or necrosis process [41] .…”
Section: Effect Of Oral Administration Of S Aethiopicum Leaves Extract On Some Biochemical Parametersmentioning
confidence: 99%